2021
DOI: 10.1111/acel.13533
|View full text |Cite
|
Sign up to set email alerts
|

Physiological clearance of Aβ by spleen and splenectomy aggravates Alzheimer‐type pathogenesis

Abstract: Background A previous study demonstrated that nearly 40%–60% of brain Aβ flows out into the peripheral system for clearance. However, where and how circulating Aβ is cleared in the periphery remains unclear. The spleen acts as a blood filter and an immune organ. The aim of the present study was to investigate the role of the spleen in the clearance of Aβ in the periphery. Methods We investigated the physiological clearance of Aβ by the spleen and established a mouse model of AD and spleen excision by removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…A recent study found that hyperactivation of monocytes and macrophages in MCI patients contributes to the AD progression 44 . Monocytes in spleen could clear circulating Aβ and splenectomy might accelerate the development of AD 45 . Under the long-term high plasma levels of Aβ 1−42 stimulation, typical monocytes recruit to various damaged sites of the body rapidly, and the proportions of monocytes in spleen were increased.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that hyperactivation of monocytes and macrophages in MCI patients contributes to the AD progression 44 . Monocytes in spleen could clear circulating Aβ and splenectomy might accelerate the development of AD 45 . Under the long-term high plasma levels of Aβ 1−42 stimulation, typical monocytes recruit to various damaged sites of the body rapidly, and the proportions of monocytes in spleen were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Y maze test with spontaneous alternation performance was conducted according to our previous study (Yu et al, 2021). The Y maze was consisted of three identical arms connected in the center with 120‐degree angle.…”
Section: Methodsmentioning
confidence: 99%
“…MWM test was conducted according to protocols validated by previous publications (Chen et al, 2021; Ho et al, 2021; Yu et al, 2021). In brief, the water maze was consisted of a circular pool (100 cm in diameter) and a platform (9 cm in diameter) submerged 1.0 cm under the warm water.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the spleen monocytes/macrophages are reported to be involved in clearing amyloid beta. 52 Still, the physiological mechanisms underlying the association between the peripheral organs and AD remain unknown. In the ontology network of the spleen dataset, we noted "carbon metabolism" (node-147) and "neutrophil degranulation" (node-151).…”
Section: Biological Functions Of Protein Communities Whose Conformati...mentioning
confidence: 99%